PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN INFLASI TERHADAP HARGA SAHAM SUB SEKTOR FARMASI - Millah, Rifadhatul; Susilowati, Dwi; Hadi, Syamsul (Program Studi Ekonomi Pembangunan, 2024)
The pharmaceutical industry is the fourth largest non-oil and gas manufacturing industry contributing to the national economy. With its strong potential and being one of the engines of economic growth, the pharmaceutical industry plays an important role in the industrial landscape in Indonesia. The aim of this research is to analyse the influence of capital structure, profitability and inflation on pharmaceutical stock prices. The population in this research are companies operating in the pharmaceutical sector and listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sample method for this research uses a purposive sampling method, namely companies that always publish financial reports for 5 periods from 2017 to 2021. So a sample of 6 pharmaceutical companies was obtained with a total of 12 observation data. This research uses secondary data with research data collection techniques in the form of documentation methods. The data analysis used is panel data regression analysis. The results of this research show that together capital structure, profitability and inflation have a positive and significant influence on pharmaceutical stock prices, where if the values ​​of these three variables increase, pharmaceutical stock prices will also increase.